Fabrication of Superhydrophobic Nanocomposite Coatings Using Polytetrafluoroethylene and Silica Nanoparticles. (13th June 2011) - Basu, Bharathibai J.; Dinesh Kumar, V.
Abstract : Superhydrophobic nanocomposite coatings were fabricated by incorporating hydrophobically modified silica (HMS) nanoparticles in polytetrafluoroethylene (PTFE) emulsion. Hydrophobicity of the coating was dependent on the concentration of HMS. Coatings containing optimum amounts of PTFE and HMS exhibited superhydrophobic property with high water contact angle (WCA) of 165 ∘ and low sliding angle <2 ∘ . Scanning electron microscopic (SEM) studies have shown a binary surface topography composed of microbumps and nanoscale granules. The synergistic effect of the micro-nano-binary structure and low surface energy of PTFE was responsible for the superhydrophobicity of the coating. The method is simple and cost-effective and can be used for preparing self-cleaning superhydrophobic coatings on large areas of different kinds of substrates like glass, metal, and composites.